PENGEMBANGAN ALAT PIROLISIS UNTUK PENGOLAHAN LIMBAH PLASTIK MENGGUNAKAN TEKNOLOGI BARU DENGAN PENDINGIN CHILLER - Naffa Eka Setiawati; Praisela Ivane Stefandra Stefandra; Muhammad Rizqi Putra Dermawan; Rahmat Dani Firmansyah; Ariel Rizantha Firstnanda (Teknik Kimia ITN Malang, 2024)
This research examines the development of a pyrolysis tool to convert HDPE, PET and PS plastic waste into oil. This research was driven by the increasing problem of plastic waste and its negative impact on the environment. This research aims to determine the quality of oil produced from plastic waste by varying process temperatures and to reduce plastic waste in society. This research uses a pyrolysis tool that has been modified with the addition of a chiller to increase the efficiency and quality of the pyrolysis process. The research results show that the pyrolysis equipment modified with a chiller can produce higher quality and more efficient oil. This research also shows that this pyrolysis tool can be used to reduce plastic waste in society.